Sierocińce zakonne w Drugiej Rzeczypospolitej. Z badań nad dziejami opieki zastępczej (pozarodzinnej) w Polsce - Bartkowiak, Edyta (Karkonoska Państwowa Szkoła Wyższa, 2011)
Child foster care organized by nuns and meant for children deprived of infamily upbringing dates back as far as the 13 century. The prototypes of orphanages run by nuns were medieval hospitals, that is care institutions for all those in need. The beginnings of care/educational work with orphaned and abandoned children are connected with the activity of The Holy Spirit de Saxia male congregation, whose members were called “duchaki” in Poland. Since the 16 century the members of the Sisters of Mercy and Sisters of Charity congregations have specialized in institutional foster care. In nationally sovereign Druga Rzeczpospolita orphanages run by nuns were numerous and they were characterized by relative financial stability, the continuity of educational processes and creativity in finding new solutions to be used in the work with the children who were cared for.
Keywords: dom dziecka; opieka zastępcza; szpitale; nuns